Total Flavonoid Content and Antioxidant Activity of Temu Mangga (Curcuma mangga Val. & Zijp) and its Classification with Chemometrics - Yuniar Intan Hartono; Indah Widyastuti; Hanna Zaidah Luthfah; Rosy Islamadina; Adelin Theresia Can; Abdul Rohman (Journal of Food and Pharmaceutical Sciences, 2020)
Indonesia is a rich country in terms of its biodiversity. Herbs that are widely used tomaintain a healthy body comes from the Zingiberaceae family, including temu mangga. Temu mangga(Curcuma mangga Val. & Zijp) is effective for relieving gastric pain, diarrhea, menstrual pain, acneand ulcers, and increasing appetite. Besides, temu mangga is considered to have antioxidant activitydue to the presence of the phenolic and flavonoid compounds. This study aims to determine thecorrelation and classification of temu mangga from various places based on total flavonoid contentand antioxidant activities. The samples were extracted with methanol, then tested for totalflavonoid content by AlCl3 method and antioxidant activity by DPPH free radical capture method.Analysis was performed using correlation coefficient value and chemometrics PCA (PrincipalComponent Analysis) and CA (Cluster Analysis) to see the relationship between total flavonoidcontent with their antioxidant activity and to see their classification. Total flavonoid content ofmethanolic extract of temu mangga gives a moderate correlation to its antioxidant activity with r =-0.6085 and clustering samples successfully determined by PCA and CA which resulted in 4 groups.Keywords: Curcuma mangga Val. & Zijp, Methanolic Extract, Flavonoid, Antioxidant, PCA, CA